The impact of (un)conventional expansionary monetary policy on income inequality - Lessons from Japan - Karl-Friedrich Israel; Sophia Latsos (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2019)
This paper analyzes the impact of conventional and unconventional monetary policy on income inequality in Japan, using hitherto unexplored data from the Japan Household Panel Survey. Empirical evidence shows that expansionary monetary policy in Japan has contributed to diminishing the gender pay gap, but also to increasing the education pay gap. These effects may have materialized via the aggregate demand channel and the labor productivity channel. In contrast, expansionary monetary policy has had no significant impact on the development of the age pay gap.
Keywords: D31; D63; E52; E58; 330; income inequality; Japan; monetary policy; low interest rate policy; unconventional monetary policy; monetary easing